2002
DOI: 10.1002/jemt.10075
|View full text |Cite
|
Sign up to set email alerts
|

Polygonal epithelial cells in glomerular cell culture: Podocyte or parietal epithelial origin?

Abstract: Podocytes are unique cells with regard to morphology, their inability to proliferate in situ, and their apparent essential function for glomerular filtration and permselectivity. Upon transfer into culture conditions, polygonal epithelial cells grow out from isolated glomeruli and these cells have been postulated to represent dedifferentiated podocytes, even though they are negative for podocyte-specific markers and undergo cell division. However, it is controversial whether they originate from podocytes or pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Our findings are consistent with the observations of other investigators [3], [19], [21][23], who have already observed the distinct cellular morphologies. Interestingly, these investigators have also observed both morphologies emerging from glomeruli independent of the presence of a capsule with PECs.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are consistent with the observations of other investigators [3], [19], [21][23], who have already observed the distinct cellular morphologies. Interestingly, these investigators have also observed both morphologies emerging from glomeruli independent of the presence of a capsule with PECs.…”
Section: Discussionsupporting
confidence: 94%
“…These findings corroborate the notion that they originate from PECs, which remains controversial. 57 GJIC has been demonstrated in vitro to have opposite effects on cell injury. Exposure of cells to irradiation or treatment with ganciclovir of herpes simplex virus thymidine kinase-transduced cells induces injury or death in not only the irradiated cells or the herpes simplex virus thymidine kinase-transduced cells but also adjacent nonirradiated cells or nontransduced cells.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas it was previously reported that human glomerular epithelial cells were sensitive to Shiga toxin in vitro only at a much higher dose (27), the cells used prior were likely to be glomerular parietal epithelial cells rather than podocytes. This supposition is supported by their isolation using a sieving procedure shown to create cultures of nonpodocyte glomerular epithelial cells, their adoption of cobblestone as opposed to arborized morphology, and their lack of expression of the podocyte marker WT-1 (41,75,76).…”
Section: Vol 77 2009mentioning
confidence: 99%